Studying local earthquakes in the area Baltic-Bothnia Megashear using the data of the POLENET/LAPNET temporary array - Usoltseva, Olga; Kozlovskaya, Elena (Solid Earth, 2016)
Earthquakes in areas within continental plates are still not completely understood, and progress on understanding intraplate seismicity is slow due to a short history of instrumental seismology and sparse regional seismic networks in seismically non-active areas. However, knowledge about position and depth of seismogenic structures in such areas is necessary in order to estimate seismic hazard for such critical facilities such as nuclear power plants and nuclear waste deposits. In the present paper we address the problem of seismicity in the intraplate area of northern Fennoscandia using the information on local events recorded by the POLENET/LAPNET (Polar Earth Observing Network) temporary seismic array during the International Polar Year 2007–2009. We relocate the seismic events using the program HYPOELLIPS (a computer program for determining local earthquake hypocentral parameters) and grid search method. We use the first arrivals of P waves of local events in order to calculate a 3-D tomographic P wave velocity model of the uppermost crust (down to 20 km) for a selected region inside the study area and show that the velocity heterogeneities in the upper crust correlate well with known tectonic units. We compare the position of the velocity heterogeneities with the seismogenic structures delineated by epicentres of relocated events and demonstrate that these structures generally do not correlate with the crustal units formed as a result of crustal evolution in the Archaean and Palaeoproterozoic. On the contrary, they correlate well with the postglacial faults located in the area of the Baltic-Bothnia Megashear (BBMS). Hypocentres of local events have depths down to 30 km. We also obtain the focal mechanism of a selected event with good data quality. The focal mechanism is of oblique type with strike-slip prevailing. Our results demonstrate that the Baltic-Bothnia Megashear is an important large-scale, reactivated tectonic structure that has to be taken into account when estimating seismic hazard in northern Fennoscandia.